2015
DOI: 10.1183/16000617.00006114
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure to pesticides and respiratory health

Abstract: Respiratory effects of environmental exposure to pesticides are debated. Here we aimed to review epidemiological studies published up until 2013, using the PubMed database. 20 studies dealing with respiratory health and non-occupational pesticide exposure were identified, 14 carried out on children and six on adults.In four out of nine studies in children with biological measurements, mothers' dichlorodiphenyldichloroethylene (DDE) blood levels during pregnancy were associated with asthma and wheezing in young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 43 publications
4
50
0
2
Order By: Relevance
“…The high‐intensity use of organophosphate (OP) pesticides has contributed to morbidity and mortality in farmworkers and their families through acute or chronic pesticide‐related illnesses . Recently, the long‐term effects of pesticide exposure have been associated with many diseases . The Phytoner study reported an association between chronic exposure to pesticides and cognitive impairment .…”
Section: Introductionmentioning
confidence: 99%
“…The high‐intensity use of organophosphate (OP) pesticides has contributed to morbidity and mortality in farmworkers and their families through acute or chronic pesticide‐related illnesses . Recently, the long‐term effects of pesticide exposure have been associated with many diseases . The Phytoner study reported an association between chronic exposure to pesticides and cognitive impairment .…”
Section: Introductionmentioning
confidence: 99%
“…This was supported by several pieces of evidence, including those suggesting that PAHs are formed mainly by organic fuel combustion and released into the atmosphere (Baek et al, 1991), where they can contribute to risk factors for respiratory cancer and childhood asthma (Bosetti et al, 2007;Karimi et al, 2015;Rota et al, 2014). A meta-analysis study concluded that the relationship between pesticide exposure and respiratory health is controversial (Mamane et al, 2015), and several other studies suggest that occupational exposure to pesticides increases the risks of developing asthma (Fareed et al, 2013;Ye et al, 2013). However, there is little epidemiological evidence to support the relationship between PFC exposure and asthma in humans (Dong et al, 2013), although a study in mice indicated a possible association (Fairley et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…The pesticide exposure of farmers' families, especially children, can be potentially significant as there is a combination of para-occupational, environmental and domestic exposures (Silvério et al, 2017). Residential exposure depends on proximity of the house to areas treated with pesticides, the persistence of pesticides used in or around the home and domestic uses at home on pets (flies and ticks) and also on humans (lice and scabies) (Bouvier et al, 2005;Mamane et al, 2015). Direct exposure to pesticides can occur during the application whereas indirect exposure of farm spouses and children to pesticides can occur through spray drift, transfer of contaminated dust and soil from treated fields to farm vehicles and buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Key words: Environmental pesticides 'exposure, Adolescent females, AChE ,Menstrual and Neurobehavioral disorders. such as endocrine disruption, blood and neurobehavioral disorders as well as the possibility of an increased risk of cancer especially, childhood cancers such as Non-Hodgkin lymphoma and leukemia (Clayton et al, 2003;Mamane et al, 2015).…”
Section: Introductionmentioning
confidence: 99%